2020
DOI: 10.3390/ijms22010076
|View full text |Cite
|
Sign up to set email alerts
|

Remodeler Catalyzed Nucleosome Repositioning: Influence of Structure and Stability

Abstract: The packaging of the eukaryotic genome into chromatin regulates the storage of genetic information, including the access of the cell’s DNA metabolism machinery. Indeed, since the processes of DNA replication, translation, and repair require access to the underlying DNA, several mechanisms, both active and passive, have evolved by which chromatin structure can be regulated and modified. One mechanism relies upon the function of chromatin remodeling enzymes which couple the free energy obtained from the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 137 publications
(282 reference statements)
0
5
0
Order By: Relevance
“…Different lines of evidence suggested that nucleosome remodelers may interact with nucleosomes at defined yet different sites, including super helical locations SHL+2, SHL−6, and the dyad axis (reviewed in Morgan et al [2021] ). In particular, recent cryo-EM analysis showed that human SMARCAD1 engages in an unusual contact with nucleosomes at the dyad axis, but the overall resolution was too low to unambiguously dock the Fun30 ATPase and especially to detect the SAM-key ( Markert et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different lines of evidence suggested that nucleosome remodelers may interact with nucleosomes at defined yet different sites, including super helical locations SHL+2, SHL−6, and the dyad axis (reviewed in Morgan et al [2021] ). In particular, recent cryo-EM analysis showed that human SMARCAD1 engages in an unusual contact with nucleosomes at the dyad axis, but the overall resolution was too low to unambiguously dock the Fun30 ATPase and especially to detect the SAM-key ( Markert et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Histone H1 binds DNA near the entry and exit sites along the nucleosome core particles and functions to stabilize the nucleosome and compact the chromatin fiber ( 66 69 ). Chromatin remodelers actively alter nucleosome positioning and may promote or prevent HP1 interactions ( 70 73 ). Further theoretical development is needed to address the interplay between HP1 binding and nucleosome remodelers, given the non-equilibrium nature of their actions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Hyde et al [ 11 ] suggested that epigenetics works as the interface between the individual and its environment to provide phenotypic plasticity to increase their adaptation capabilities [ 11 ]. Some of the epigenetic mechanisms that act in modulating gene expression are DNA methylation [ 15 ], DNA acetylation [ 67 ], histone modifications [ 68 ], nucleosome repositioning [ 69 ], and small interfering RNAs [ 16 ]. These biological mechanisms help cells to differentiate not only morphologically, but also functionally, controlling the genomic regions that will be accessed and/or expressed.…”
Section: Epigeneticsmentioning
confidence: 99%